Serum Endocan Level as a Predictive Marker for Hemodynamically Significant Patent Ductus Arteriosus in Very Low Birth Weight İnfants - Halil, Halit; Tayman, Cuneyt; Cakır, Ufuk; Buyuktiryaki, Mehmet; Serkant, Utku; Oğuz, Serife Suna (American Journal of Perinatology, 2017)
Background Diagnosis and treatment of patent ductus arteriosus (PDA) in premature infants is still an important problem for clinicians. Echocardiography is the gold standard for determination of PDA based on clinical and hemodynamic significance. Clinical decision making may be aided by measuring circulating biomarkers such as natriuretic and endothelial propeptides. We aimed to investigate the significance of serum endocan and B-type natriuretic peptide (BNP) in the diagnosis and follow-up of hemodynamically significant PDA (hsPDA) in very low birth weight infants.Materials and Methods In this study, 84 premature infants with gestation age less than 32 weeks were included. Forty-two premature infants with hsPDA were determined as the study group and 42 premature infants without PDA were assigned as the control group. Blood samples were collected and analyzed for serum endocan and pro-BNP levels.Results Serum levels of pro-BNP and endocan in the study group at the time of diagnosis of PDA were found to be significantly higher than the control group, and the levels decreased significantly after medication. Multivariate regression analysis showed that birth weight and the presence of PDA were significantly correlated with serum endocan levels. The cutoff values of pro-BNP and endocan for PDA prediction were 290 pg/mL and 506 ng/mL, respectively.Conclusion Endocan and pro-BNP assays have clinical importance in the diagnosis, initiation therapy, and follow response to therapy in very low birth weight infants with hsPDA.
Keywords: endocan; pro-BNP; patent ductus arteriosus; biomarkers; preterm neonates